Explaining geopolitical components affecting the strategic linkages of countries Case Study: Iran and Iraq (تحقیقات کاربردی علوم جغرافیایی)
In the current disorderly world, securing benefits and achieving optimal security for countries alone is very difficult and unavoidable. Uniting with other countries and powers is a way to advance national goals and provide benefits, and bring more guarantees for countries to survive, advance, develop and peace. The factors and conditions that lead to the unification of the countries have been a lot of controversy and debate and have been analyzed from a variety of perspectives. Although geographic proximity and geographical similarity seem to be the prelude to creating unity between countries, the Iranian-Iraqi model in the Middle East is challenging this claim. Except for a few days in the early 20th century, the two countries were in conflict with the majority of the century, even an eight-year-old war between them. So the main question of this research is how geopolitical factors contribute to the unification of countries, and what are these factors and components in the strategic relationship between Iran and Iraq? This research is descriptive and based on library and document data. The results of the study show that the components of the internal environment (economic, socio-cultural components, geographic and political components, security and geopolitics), the regional external environment and, ultimately, the global environment have affected the quality and quantity of the strategic linkage of Baghdad-Tehran. The strategic link between the two countries is a function of the accompaniment and positive function of the triangle, which itself is based on more complex components.